1981
DOI: 10.1093/nar/9.14.3251
|View full text |Cite
|
Sign up to set email alerts
|

The structure of the gene for the large subunit of ribulose 1,5-bisphosphate carboxylase from spinach chloroplast DNA

Abstract: A cloned fragment of spinach chloroplast DNA carrying the gene for the large subunit of ribulose bisphosphate (RuBP) carboxylase has been analysed by electron microscopy of R-loops, by hybridization to Northern blots of chloroplast RNA, by S1 nuclease mapping and by DNA sequencing. The transcribed region of the gene is 1690 +/- 3 nucleotides long and co-linear with its mRNA. It comprises a 178-179 bp 5' untranslated sequence, a 1425 bp coding region and an 85-88 bp 3' untranslated region. The deduced sequence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
175
1
1

Year Published

1983
1983
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 387 publications
(183 citation statements)
references
References 43 publications
5
175
1
1
Order By: Relevance
“…For trnL-F regions, primers c, d, e, and f as in Taberlet et al (1991) were used with the internal primers d and e used only for degraded DNA. For rbcL, primers Z1 and 3' (Zurawski et al, 1981;Olmstead et al, 1993) were used. In taxa for which the primer 3' failed to produce any readable sequences, another primer Z1204R was used (Zurawski et al, 1981).…”
Section: Dna Extraction and Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…For trnL-F regions, primers c, d, e, and f as in Taberlet et al (1991) were used with the internal primers d and e used only for degraded DNA. For rbcL, primers Z1 and 3' (Zurawski et al, 1981;Olmstead et al, 1993) were used. In taxa for which the primer 3' failed to produce any readable sequences, another primer Z1204R was used (Zurawski et al, 1981).…”
Section: Dna Extraction and Sequencingmentioning
confidence: 99%
“…For rbcL, primers Z1 and 3' (Zurawski et al, 1981;Olmstead et al, 1993) were used. In taxa for which the primer 3' failed to produce any readable sequences, another primer Z1204R was used (Zurawski et al, 1981). The following pairs were employed for the markers:…”
Section: Dna Extraction and Sequencingmentioning
confidence: 99%
“…On the basis of available crystallographic (Andersson et al, 1989; Knight at al., 1989;1990;Taylor and Andersson, 1997) and gene struc tures (McIntosh et al, 1980;Zurawski et al, 1981;Shinozaki and Sugiura, 1982;Zurawski et al, 1986) which revealed the 123 residues for the small su bunit and 475 amino acid residues for the large subunits we have calculated the amino acid com positions of other native rubisco enzymes and sys tematically compared them with barley rubisco (Table II). Major differences have been observed in the amino acid composition of barley rubisco, where the concentration of Cys, Ser, Thr, lieu, Leu, Arg and Trp residues are quite variable as compared to the other higher plants.…”
Section: P D Oh Alsk A-a N G Elo V a Et Al ■ Purification C H Aracmentioning
confidence: 99%
“…The importance of rubisco in photosynthesis and photorespiration makes it a major object for many structural and functional studies (for re view see, Schneider et al, 1992; Hartman and The crystal and the gene structures of many higher plant rubisco enzymes and its subunits have been well established with spinach (Spinacia oleracea L., Taylor and Andersson, 1997;Zurawski et al, 1981;Knight et al, 1989), to bacco (Nicotiana tabacum L., Shinozaki and Sugiura, 1982;Mazur and Chui, 1985;Chapman et al, 1987;Chapman et al, 1988), maize (Zea mays L., McIntosh et al, 1980;Zurawski et al, 1984), pea (Pisum sativum L., Zurawski et al, 1986) and the partial gene sequence of the large su bunit from barley (Hordeum vulgare L., Zuraw ski et al , 1984). Results of these studies revealed that in most of the photosynthetic organisms, including higher plants, rubisco is a hexadecamer (Mr. 560 kDa) consisting of eight large (LS) and eight small (SS) subunits in an L8S8 arrangement.…”
Section: Introductionmentioning
confidence: 99%
“…Since amino acid sequences of spinach Rbu(l,5)P2ase subunits contain 10 cysteines (9 in the L subunit and 1 in the S subunit, see Martin, 1979;Zurawski et al, 1981), we reexamined the thiol content of the spinach enzyme. The presence of three cysteines in the S subunit was revealed by titration of thiol groups in preparations of S subunits that were isolated according to Andrews and Lorimer (1985), and by analysis of carboxymethylated S subunit following the reaction of spinach Rbu(l,S)P2ase with iodo[14C]acetate.…”
Section: Mechanism Of Disulfide Formationmentioning
confidence: 99%